2020
DOI: 10.1093/mnras/staa205
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational waves from fast-spinning white dwarfs

Abstract: Two mechanisms of gravitational waves (GWs) emission in fast-spinning white dwarfs (WDs) are investigated: accretion of matter and magnetic deformation. In both cases, the GW emission is generated by an asymmetry around the rotation axis of the star. However, in the first case, the asymmetry is due to the amount of accreted matter on the magnetic poles, while in the second case it is due to the intense magnetic field. We have estimated the GW amplitude and luminosity for three binary systems that have a fast-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
(124 reference statements)
1
14
0
Order By: Relevance
“…These are WD pulsars, so they can emit both EM and GW radiations. Recently, Sousa et al (2020a) attempted to explain the emission of GWs including the mass accretion from the binary companion as well as the magnetic deformation. However, their study lacked proper source modelling because they considered the magnetic field inside the WD to be a dipole only.…”
Section: Detection Of Wd Pulsarsmentioning
confidence: 99%
“…These are WD pulsars, so they can emit both EM and GW radiations. Recently, Sousa et al (2020a) attempted to explain the emission of GWs including the mass accretion from the binary companion as well as the magnetic deformation. However, their study lacked proper source modelling because they considered the magnetic field inside the WD to be a dipole only.…”
Section: Detection Of Wd Pulsarsmentioning
confidence: 99%
“…On the other hand, recent detection of GWs from the merger events opens a new window in astronomy. Since a strong magnetic field and high rotation can increase the mass of a WD, such a WD, possessing a specific configuration, can emit GW efficiently (Kalita & Mukhopadhyay 2019b, 2020Sousa et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in Refs. 1,2,35, it has been suggested that rotating magnetized WDs can emit continuous GWs with amplitudes possibly detected by upcoming GW detectors such as LISA, DECIGO and BBO. Here we revisit our two works [Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Here we revisit our two works [Refs. 1,2], where we investigate two mechanisms of gravitational radiation emission in fast-rotating magnetized WD: matter accretion and magnetic deformation. In both cases, the emission in GW is produced by the asymmetry around the star's rotation axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation